Charting and analyzing the catch distribution of Japan’s coastal fisheries resources based on centennial statistics - Watari, Shingo; Takemura, Shion; Oyaizu, Hitomi (Frontiers in Marine Science, 2024)
Spatiotemporal changes in catches and transition of fishing grounds have been observed in various coastal fishery resources in Japanese waters in recent years. Are these changes part of cyclical fluctuations on a centennial timescale? Are these changes situations that have never been observed prior to this? Are common factors included in the long-term fluctuations among coastal fisheries resources? A total of 12 important Japanese coastal fisheries resources including fishes, shells, invertebrates, and algae were analyzed using fisheries statistics on the geographical center of catch compiled since 1894. The time series of the geographical center of catch showed a cyclical fluctuation trend over time rather than changing monotonically. The geographic center of catch in recent years (2019-2021) was located at the northeastern margin of the distribution, compared to its location since the end of the 19th century for many fishery resources. For coastal fishery resources, the situation in terms of fluctuations in the geographical center of catch is more extreme than in the past 100 years. The results of the dynamic factor analysis suggested that the state of these resources may be affected by the global ocean environment and other factors including human activities. Examining how fisheries have responded to past cyclical fluctuations may provide insight into adapting to the current rapid changes caused by climate change.